Fungal Production of Cellulase Using Fruit Waste as Economical Growth Substrates - M. Imran Hussain, Iqra Ijaz,, M. Ahmad Mustafa, Neelam Sabar, S. M. Umar Kazmi, Aamirgul Memon, Momina Najeeb, M. Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Vegetables and fruits are playing an important role in human life and diet. For eco-friendly usage the fruit peel wastes can be used as nutrients for microorganisms and animals as they consist of various growth promoting factors. Cellulolytic enzymes convert cellulose into simpler sugars. Due to suitable cellulase titers and rapid growth bacteria and fungi are becoming choice of interest. Aim: Production of fungal cellulase by using different types of fruit wastes. Method:This descriptive study was conducted by collecting the Fruit wastes (mango peels, melon peels, orange peels and watermelon rind) from fruit processing shops and transported to Applied and Environmental Microbiology laboratory.Inoculum was prepared by using basal medium and fruit peel powder.Descriptive statistical analysis of data will be performed. One way Analysis of Variance (ANOVA) will be applied for comparing mean values among species using Minitab 16. P < 0.05 will be considered significant. Result: The statistical analysis showed that in solid state fermentation the enzyme summary within 10 days was (181.32±0.00 μg/ml/min) after every 24 hour was (9.40±1.22μg/ml/min) and (0.39±0.05μg/ml/min) after every 1 hour and (0.01±0.00μg/ml/min) at 1 minute. The statistical analysis showed that in sub-merged fermentation the enzyme summary within 10 days was 191.83±4.96 after every 24 hour was (7.12±0.76μg/ml/min) and (0.30±0.03μg/ml/min) after every 1 hour and (0.0.00±0.00 μg/ml/min) at 1 minute. Conclusion: The present study clearly indicates the potential of Rhizopussp as the best producer of cellulolytic enzymes. Regarding the substrate fruit peels (mango peels, melon peels, orange peels, and watermelon rind) can be used for the efficient production of cellulase. Keywords: Rhizopus, cellulolytic enzymes, fruit peels, fungal production.